Techno Economic Analysis Of Relay Connectivity Using Satellites With Geo Infrastructure To Reach Telecommunications Blank Spot Areas - Wicaksono, Andika Budi; Sudjai, Miftadi; Astuti, Rina Pudji (Green Publisher Indonesia, 2026)
With such a large number of islands and populations, there is a big problem in Indonesia, namely telecommunication problems. The main problem in the telecommunications sector in Indonesia is the difficulty of developing wireless and cable network infrastructure so that it cannot reach all regions. The purpose of this study is to determine the efficiency of capex and opex related to the use of GEO satellites to integrate between BTS HUBs on Sapudi Island in terms of link budget and techno economic analysis. The Link Budgeting analysis is based on the availability of Base Station Controller (BSC) at the transmitting ground station in the city of Surabaya and on the availability of the receiver VSAT, namely BTS located on Sapudi island, both of which are connected to the GEO Nusantara Satu satellite. Techno economic analysis is carried out by adopting Capital Budgeting analysis. The elements that make up Capital Budgeting include Capex consisting of RAN, MW, Power, VSAT and Tower in VSAT and FO. Opex consists of maintenance, NOC, Monthly Lease, Annual ISR and Drive Test as well as VSAT and FO. Potential Revenue in this study is the value of income obtained from USO funds (operator involvement). Model simulations, both budget and techno economic link, were validated by consulting the model with academic collaborators, namely supervisors. The results of the study show that technically, the application of GEO satellites on Sapudi Island has a low Carrier To Noise (C/N) value with a value of 13.90 dB